Patient Preferences for Use of Archived Biospecimens from Oncology Trials When Adequacy of Informed Consent Is Unclear. (6th September 2019) - Peppercorn, Jeffrey; Campbell, Eric; Isakoff, Steve; Horick, Nora K.; Rabin, Julia; Quain, Katharine; Sequist, Lecia V.; Bardia, Aditya; Collyar, Deborah; Hlubocky, Fay; Mathews, Debra
Abstract: Background: Oncology research increasingly involves biospecimen collection and data sharing. Ethical challenges emerge when researchers seek to use archived biospecimens for purposes that were not well defined in the original informed consent document (ICD). We sought to inform ongoing policy debates by assessing patient views on these issues. Materials and Methods: We administered a cross‐sectional self‐administered survey to patients with cancer at an academic medical center. Survey questions addressed attitudes toward cancer research, willingness to donate biospecimens, expectations regarding use of biospecimens, and preferences regarding specific ethical dilemmas. Results: Among 240 participants (response rate 69%), virtually all (94%) indicated willingness to donate tissue for research. Most participants (86%) expected that donated tissue would be used for any research deemed scientifically important, and virtually all (94%) expected that the privacy of their health information would be protected. Broad use of stored biospecimens and data sharing with other researchers increased willingness to donate tissue. For three scenarios in which specific consent for proposed biobank research was unclear within the ICD, a majority of patient's favored allowing the research to proceed: 76% to study a different cancer, 88% to study both inherited (germline) and tumor specific (somatic) mutations, and 70% to permit data sharing. A substantial minority believed that research using stored biospecimens should only proceed with specific consent. Conclusion: When debates arise over appropriate use of archived biospecimens, the interests of the research participants in seeing productive use of their blood or tissue should be considered, in addition to addressing concerns about potential risks and lack of specific consent. Abstract : Ethical challenges emerge when researchers seek to use archived biospecimens for purposes that were not well defined in the original informed consent document. This article assesses the patient's perspective on the subject.